O Mulltiano no Rio Mapuá/Município de Breves: vivências, currículo e aprendizagem na comunidade e escola Santa Maria - SILVA, Edieuza Maria da (2022)
This study presents as a theme "The Multiano in the Rio Mapuá / Municipality of Breves: Experiences, Curriculum and Learning in the Community and Santa Mari School". A study that shows the teaching trajectory in relation to transportation to reach the riverside community, the difficulties faced during the long journey, as well as the accumulated risks, with the educational reality, without pedagogical support and adequate materials to develop their daily classes. However, this study also shows the persistence in having students' learning positives, mixing local knowledge and cultures, oral experiences, telling stories and stories, inserted in the school's annual curriculum, thus making students feel part of the education and showing the value of the mother tongue for teaching and learning. Showing mainly that local knowledge can become scientific and contribute to new learning. This research was carried out in the community and school Salta Maria do Alto Mapuá, in the Municipality of Breves. As methodology, the interview, observation and personal experience as a teacher of the community was used. As a theoretical basis, we sought the studies of Hall (2005) and the question of the culture that surrounds the subject and of which it forms part forming its identity. In Giddens (1997) with the importance of looking to the past as a way of orientation to the current and future life. Also in Candau (2008) with the social struggles for the valorization of the experiences, Marcuschi and the contextualization and explicitness in the relation between speech and writing, besides other authors important for this production and learning.